(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Steshenko V. V., Musayev K.F., Belikova M. V. Genesis and formation of future children’s technical creativity leaders’ methodical training in the XX-th century. Peculiarities of genesis and formation of future pupils’ extracurricular technical creativity leaders’ methodical training are described in the article. The need for its foundation is proved to be caused by the rapid development of scientific and technical progress in the beginning and in the middle of the twentieth century. The authors reveal the basics of future specialists training which were laid down by scientists and educators.